Gerakan Literasi Sekolah Dan Lingkungan Kaya Teks Di Sekolah “Studi Asesmen Diri Sekolah Menengah Pertama Di Surabaya” - Layli Hidayah; Ganjar Setyo Widodo (Jurnal Bidang Pendidikan Dasar, 2020)
Abstract: Based on the results of the tests conducted by PISA in 2012 and 2015, there were no significant differences in the ability of students in Indonesia, of which has been still relied on the lower ranks. Even though the school literacy movement (SLM) has been promoted by the government since then, there tends shows a lot of problems and neglect factors related to school policy-makers and the teachers. This self-evaluation study was carried out by involving private secondary school levels in Surabaya to study the achievements of the implementation of the SLM in their school, in particular related with the creation of text-rich environment. The results of this study are expected to provide preliminary research findings on a text-rich environment for the success of GLS in Surabaya. In addition, reflections involving teachers provide an understanding of the concept of literacy among teachers still based on reading and writing activities, not on information literacy and so on. The limitations of this understanding make the development of a text-rich environment in schools very minimal. Abstrak: Berdasarakn hasil tes yang dselenggarakan oleh PISA di tahun 2012 dan 2015 tidak ada perbedaan yang menonjol dalam kemampuan literasi siswa di Indonesia, dan Indonesia masih berada pada peringkat bawah. Sekalipun gerakan literasi sekolah (GLS) sudah digalakkan, tampaknya masih banyak masalah dan kealpaan informasi terkait dengan budaya literasi di sekolah, baik pemangku kebijakan sekolah maupun guru. Penelitian evaluasi diri ini dilaksanakan dengan melibatkan sekolah menengah swasta di Surabaya untuk mengetahui capaian pelaksanaan GLS, terutama penciptaan lingkungan kaya teks. Hasil dari penelitian ini diharapkan mampu memberikan pemetaan awal penciptaan lingkungan kaya teks terhadap kesuksesan GLS di Surabaya. Selain itu, refleksi yang melibatkan guru memberikan gambaran bagaimana pemahaman konsep literasi di antara guru masih berpatok pada aktivitas membaca dan menulis, belum pada literasi informasi dan seterusnya. Keterbatasan pemahaman ini membuat pengembangan lingkungan kaya teks di sekolah juga terlambat